Phosphatase and Tensin Homology Deleted on Chromosome 10 Inhibitors Promote Neural Stem Cell Proliferation and Differentiation - Liu, Xiaojiang; Cui, Yiqiu; Li, Jun; Guan, Cheng; Cai, Shu; Ding, Jinrong; Shen, Jianhong; Guan, Yixiang (Frontiers in Pharmacology, 2022)
Phosphatase and tensin homology deleted on chromosome 10 (PTEN) is a tumor suppressor gene. Its encoded protein has phosphatase and lipid phosphatase activities, which regulate the growth, differentiation, migration, and apoptosis of cells. The catalytic activity of PTEN is crucial for controlling cell growth under physiological and pathological conditions. It not only affects the survival and proliferation of tumor cells, but also inhibits a variety of cell regeneration processes. The use of PTEN inhibitors is being explored as a potentially beneficial therapeutic intervention for the repair of injuries to the central nervous system. PTEN influences the proliferation and differentiation of NSCs by regulating the expression and phosphorylation of downstream molecular protein kinase B (Akt) and the mammalian target of rapamycin (mTOR). However, the role of PTEN inhibitors in the Akt/mTOR signaling pathway in NSC proliferation and differentiation is unclear. Dipotassium bisperoxo (picolinoto) oxovanadate (V) [bpv(pic)] is a biologically active vanadium compound that blocks PTEN dephosphorylation and suppresses its activity, and has been used as a PTEN lipid phosphatase inhibitor. Here, bpv(pic) intervention was found to significantly increase the number of rat NSCs, as determined by bromodeoxyuridine staining and the cell counting kit-8, and to increase the percentage of neurons undergoing differentiation, as shown by immunofluorescence staining. Bpv(pic) intervention also significantly increased PTEN and mTOR expression, as shown by real-time PCR analysis and western blotting. In conclusion, PTEN inhibitor bpv(pic) promotes the proliferation and differentiation of NSCs into neurons.